Identifying “at-risk” patients for sub-optimal beta-lactam exposure in critically ill patients with severe infections - Abdul Aziz, Mohd. Hafiz; Lipman, Jeffrey; Roberts, Jason A. (BioMed Central, 2017)
Pathophysiological changes affecting drug pharmacokinetics Mortality due to severe infections in the intensive care unit (ICU) remains high despite recent therapeutic advancements [1]. However, appropriate antibiotic administration (including spectrum of activity and therapeutic exposure) is rarely a straightforward process in ICU patients as they commonly develop extreme pathophysiological changes that can alter antibiotic pharmacokinetics and consequently affect drug exposure in this population. The volume of distribution and drug clearance are the pharmacokinetic parameters of greatest relevance to determining drug dosing requirements, and both parameters may be significantly deranged during critical illness [2, 3]. Furthermore, ICU pathogens are relatively different from those in the general wards as they commonly have reduced antibiotic susceptibility [4]. Despite profound physiological and pharmacokinetic differences to the noncritically ill population, critically ill patients are typically given conventional antibiotic dosing regimens, which increase the likelihood of therapeutic failures and the emergence of bacterial resistance [5].